Prediction of buckling mode for simply supported stiffened thin plates subject to inplane loading - Abdul Halim, Abdul Karim; Syed Mohamed Ali, Jaffar; Erwin, Sulaeman (2019)
Designing a stiffened plate with respect to a certain amount of buckling load so that it will buckle according to our desired buckling mode is a challenge. The mode of buckling either on local or global can be predicted by controlling the crossover value. The crossover is an important factor because it provides a limitation on the size of stiffener when the global buckling is to start. This paper will discuss on how to determine the crossover value in order to generate preferable mode of buckling through analytical solution for a stiffened panel. Once the size of stiffener has been defined by the crossover, Nastran software will be used to verify the mode of buckling. The model is formulated using CQUAD4 element and CBAR element for the plate and stiffener respectively. The edge conditions are simply supported and several plate thickness and stiffeners is used in the analysis. Simulation result shows the presented technique is suitable for plate that has 4 and 5 stiffeners. By adding up a stiffener, the critical buckling load can be increased twofold. This can serve as a guideline in designing a stiffened panel.